Work in a Globalizing World: Gender, Mobility, Markets. 5th Annual Seminar in History and Sociology of the Bielefeld Graduate School in History and Sociology (BGHS): April 8-10, 2013, Bielefeld University, Germany - Pustulka, Paula (Lidé města, 2013)
Although global labour is not a new phenomenon for the disciplines of social sciences and history, it has recently gained attention due to novel approaches to certain dichotomies, such as work and non-work or translocality and nation state. Furthermore, classic analytical axis of ethnicity, gender and social class, paired with crucial importance of human cross-border mobility have provided new aspects for advanced theoretical and empirical studies of globality, as it pertains to international migration, labour markets, changes brought to employments and beyond-border gender orders. As such, the 5th Annual Seminar of BGHS, held between 8th and 10th of April 2013 brought together experienced scholars as well as doctoral researchers from across disciplines, providing a space for peer-exchange of ideas and inviting contributions on conceptual, analytical and practical levels.